A study case in photoepilation, the HPPL™ and IFL™ technologies - Alessandro Martella; Mauro Raichi (PAGEPress Publications, 2017)
The High Power Pulsed Light™ [HPPL™] and Incoherent Fast Light™ technologies [IFL™, Novavision Group S.p.A., 20826 Misinto (MB), Italy] are recent innovations in the field of unwanted hair removal with intense pulsed light devices. IFL™ is a further improvement over the already advanced characteristics of the HPPL™ technology. A selection of photoepilation case histories with the HPPL™ and IFL™ technologies is presented; a short introduction highlights the main features of the two technologies. All study materials were appropriately peer-reviewed for ethical problems.